Experiences in the creation of an artistic video game as an interdisciplinary exercise in a research project (2020)
Eng: The following paper aims to share the results of a first interdisciplinary exercise developed between the programs of Systems Engineering and Audiovisual Arts of the Universidad Autónoma de Bucaramanga taking as an integrative topic the development and design of an artistic videogame in the context of a research project in the strict sense. The research sets out the methodological details carried out during the execution of the project, the experiences of work between the arts and engineering and the description of the resultant products to possibility all of them to serve as bases for future projects in this area.